Avascular necrosis of the femoral head: Assessment following developmental dysplasia of the hip management - Al Faleh, Ahmed F.; Jawadi, Ayman H.; Al Sayegh, Samir; Al Rashedan, Bander S.; Al Shehri, Mohammed; Al Shahrani, Abdullah (International Journal of Health Sciences, 2019)
Objectives: Avascular necrosis (AVN) of the femoral head is a major complication following treatment for developmental dysplasia of the hip (DDH). It is caused by excessive pressure over the femoral head, which compromises its blood supply. The rate of AVN following DDH treatment ranges from 6% to 48%. This study aimed to analyze the rate of AVN in DDH patients following different standard surgical treatments. Methodology: A retrospective cohort study was performed on patients diagnosed with DDH between January 2007 and December 2013. All idiopathic DDH patients who underwent standard surgical treatments were included in the study. Neuromuscular and teratologic patients and patients with previous surgical treatment outside the institute were excluded from the study. Results: Overall, 204 hips in 143 pediatric patients were included in the study. The majority (84.8%) of the patients were female. Most patients (82.2%) received single treatment. The most commonly used surgical treatment was open reduction with pelvic osteotomy (82.8%). Type 4 Tonnis classification of DDH was found in 62.3% of patients. AVN was found in 14.3% of our study population. The majority (57.1%) of diagnosed AVN patients showed Grade 1 (Kalamchi) AVN classification. Patients who underwent closed reduction and hip spica showed a significantly higher rate of AVN compared to other treatments (14.3%, P = 0.044). Conclusion: Close follow-up of patients treated with closed reduction is mandatory as these patients have the highest risk of AVN. We recommend the introduction of national screening programs targeting all newborn children and including systematic follow-up at well-baby clinics during the early years of life.